Penerapan Model Experiental Learning untuk Meningkatkan Hasil Belajar Siswa pada Materi Pendidikan Pancasila di SD Negeri 15 Koba - Bunga Sukmawati Yuli Sri Astuti; Fandi Nugroho; Erika Fitri Wardani (CENDEKIAWAN, 2025)
Pancasila education in elementary schools is still dominated by methods that tend to be one-way and do not involve students actively in the learning process. This has an impact on the low understanding of Pancasila values. This study aims to improve student learning outcomes in Pancasila Education material at SD Negeri 15 Koba. This study used a classroom action research approach implemented in two learning cycles. Each cycle consists of planning, implementation, observation, and reflection. This research applied the Experiental Learning model with data collection techniques through observation of teacher and student activities and learning outcomes test, the research subjects were 27 grad 6 students. The results showed a significant increase in student learning outcomes, where in the first cycle 66,67% of students reached the Criteria for Achieving Learning Objectives (KKTP), the increased to 88,89% in the second cycle. Teacher activity increased form 90,63% to 94,27% while student activity increased from 88,07% to 90,63%. The Experiental Learning model proved effective in improving understanding and implementation of Pancasila values through direct experience and meaningful reflection. This research provides a practical contribution to the development of more effective Pancasila Education learning strategies at the elementary school level, as well as providing an alternative learning model that can be adapted by teachers in teaching Pancasila values.